Use of chemical shift encoded magnetic resonance imaging (CSE-MRI) for high resolution fat-suppressed imaging of the brachial and lumbosacral plexuses. Issue 6 (June 2016) - Grayev, Allison; Reeder, Scott; Hanna, Amgad
Abstract: Purpose: In the era of increasingly complex surgical techniques for peripheral nerve repair, there is a need for high spatial resolution imaging of the neural plexuses in the body. We describe our experience with chemical shift encoded MRI and its implications for patient management. Materials and methods: IDEAL water-fat separation is a chemical shift based method of homogeneously suppressing signal from fat, while maintaining adequate signal. This technique was used in clinical practice and the patient images reviewed. Results: IDEAL water-fat separation was shown to improve visualization of the brachial and lumbosacral plexuses with good fat suppression and high signal to noise ratio. Conclusion: IDEAL water − fat separation is an excellent technique to use in the imaging of the brachial and lumbosacral plexuses as it balances the need for homogeneous fat suppression with maintenance of excellent signal to noise ratio.